Comparative transcriptome analysis of the mechanism difference in heat stress response between indica rice cultivar “IR64” and japonica cultivar “Koshihikari” at the seedling stage - Wang, Yingfeng; Wang, Yubo; Chen, Wenjuan; Dong, Yating; Zhang, Guilian; Deng, Huabing; Liu, Xiong; Lu, Xuedan; Wang, Feng; Chen, Guihua; Xiao, Yunhua; Tang, Wenbang (Frontiers in Genetics, 2023)
Heat stress (HS) has become a major abiotic stress in rice, considering the frequency and intensity of extreme hot weather. There is an urgent need to explore the differences in molecular mechanisms of HS tolerance in different cultivars, especially in indica and japonica. In this study, we investigated the transcriptome information of IR64 (indica, IR) and Koshihikari (japonica, Kos) in response to HS at the seedling stage. From the differentially expressed genes (DEGs) consistently expressed at six time points, 599 DEGs were identified that were co-expressed in both cultivars, as well as 945 and 1180 DEGs that were specifically expressed in IR and Kos, respectively. The results of GO and KEGG analysis showed two different HS response pathways for IR and Kos. IR specifically expressed DEGs were mainly enriched in chloroplast-related pathways, whereas Kos specifically expressed DEGs were mainly enriched in endoplasmic reticulum and mitochondria-related pathways. Meanwhile, we highlighted the importance of NO biosynthesis genes, especially nitrate reductase genes, in the HS response of IR based on protein-protein interaction networks. In addition, we found that heat shock proteins and heat shock factors play very important roles in both cultivars. This study not only provides new insights into the differences in HS responses between different subspecies of rice, but also lays the foundation for future research on molecular mechanisms and breeding of heat-tolerant cultivars.